The Role of Complement Activating Collectins and Associated Serine Proteases in Patients With Hematological Malignancies, Receiving High-Dose Chemotherapy, and Autologous Hematopoietic Stem Cell Transplantations (Auto-HSCT) - Świerzko, Anna S.; Michalski, Mateusz; Sokołowska, Anna; Nowicki, Mateusz; Eppa, Łukasz; Szala-Poździej, Agnieszka; Mitrus, Iwona; Szmigielska-Kapłon, Anna; Sobczyk-Kruszelnicka, Małgorzata; Michalak, Katarzyna; Gołos, Aleksandra; Wierzbowska, Agnieszka; et al. (Frontiers in Immunology, 2018)
We conducted a prospective study of 312 patients (194 with multiple myeloma, 118 with lymphomas) receiving high-dose conditioning chemotherapy and autologous haematopoietic stem cell transplantation (auto-HSCT). Polymorphisms of MBL2 and MASP2 genes were investigated and serial measurements of serum concentrations of mannose-binding lectin (MBL), CL-LK collectin and MASP-2 as well as activities of MBL-MASP-1 and MBL-MASP-2 complex were made. Serum samples were taken before conditioning chemotherapy, before HSCT and once weekly after (totally 4-5 samples); in minority of subjects also one and/or three months post transplantation. The results were compared with data from 267 healthy controls and analysed in relation to clinical data to explore possible associations with cancer and with chemotherapy-induced medical complications. We found a higher frequency of MBL deficiency-associated genotypes (LXA/O or O/O) among multiple myeloma patients compared with controls. It was however not associated with hospital infections or post-HSCT recovery of leukocytes, but seemed to be associated with the most severe infections during follow-up. Paradoxically, high MBL serum levels were a risk factor for prolonged fever and some infections. The first possible association of MBL2 gene 3’-untranslated region polymorphism with cancer (lymphoma) in Caucasians was noted. Heterozygosity for MASP2 gene +359 A>G mutation was relatively frequent in lymphoma patients who experienced bacteremia during hospital stay. The median concentration of CL-LK was higher in myeloma patients compared with healthy subjects. Chemotherapy induced marked increases in serum MBL and MASP-2 concentrations, prolonged for several weeks and relatively slighter decline in CL-LK level within one week. Conflicting findings on the influence of MBL on infections following chemotherapy of myeloma and lymphoma have been reported. Here we found no evidence for an association between MBL deficiency and infection during the short period of neutropenia following conditioning treatment before HSCT. However, we noted a possible protective effect of MBL during follow-up, and suspected that to be fully effective when able to act in combination with phagocytic cells after their recovery.